2017
DOI: 10.1038/srep43992
|View full text |Cite|
|
Sign up to set email alerts
|

The human mitochondrial transcription factor A is a versatile G-quadruplex binding protein

Abstract: The ability of the guanine-rich strand of the human mitochondrial DNA (mtDNA) to form G-quadruplex structures (G4s) has been recently highlighted, suggesting potential functions in mtDNA replication initiation and mtDNA stability. G4 structures in mtDNA raise the question of their recognition by factors associated with the mitochondrial nucleoid. The mitochondrial transcription factor A (TFAM), a high-mobility group (HMG)-box protein, is the major binding protein of human mtDNA and plays a critical role in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 60 publications
2
29
1
Order By: Relevance
“…Furthermore, other factors affect transcription elongation within CSBII. TFAM, a transcription initiation factor that binds to mtDNA, acts as a transcriptional repressor and preferentially binds to the G-quadruplex structure and stimulates the G-quadruplex barrier (37). Further studies are necessary to elucidate how TEFM contributes to mtRNAP transcription elongation through the TFAM-protected G-quadruplex structure and whether its binding plays a role in the dynamic switching between mitochondrial DNA replication and transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other factors affect transcription elongation within CSBII. TFAM, a transcription initiation factor that binds to mtDNA, acts as a transcriptional repressor and preferentially binds to the G-quadruplex structure and stimulates the G-quadruplex barrier (37). Further studies are necessary to elucidate how TEFM contributes to mtRNAP transcription elongation through the TFAM-protected G-quadruplex structure and whether its binding plays a role in the dynamic switching between mitochondrial DNA replication and transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five of the 29 most common mt-DGF sites colocalized with the "low TFAM" sites (P = 0.00065, two-tailed Fisher's exact test), whereas only 17 colocalized with the "high TFAM" sites (P = 0.69, two-tailed Fisher's exact test). It has been suggested that TFAM preferentially binds GQP sites in vitro, although in 0.75M NaCl (Lyonnais et al 2017), which is approximately five times higher than the physiological NaCl concentration (Li et al 2016), but not at 0.25 M, which is approximately twofold higher than the physiological NaCl concentrations. We found that whereas "low TFAM" sites preferentially overlapped GQP sites (83/88 of the "low TFAM" sites, P = 3.1756 × 10 −14 , twotailed Fisher's exact test as compared to control), the "high TFAM" sites did not (48/103 of the "high TFAM" sites, P = 0.19952, two-tailed Fisher's exact test as compared to control) (Supplemental Table S7).…”
Section: A Common Pattern Of Mtdna Dgf Sites In a Variety Of Human Cementioning
confidence: 99%
“…There is a long-standing controversy regarding the mtDNA-binding specificity of TFAM. Whereas some findings imply lack of mtDNA sequence binding specificity (Kanki et al 2004;Kaufman et al 2007;Kukat et al 2015), others proposed that TFAM has binding preferences to certain regions (Ghivizzani et al 1994) and in vitro preferences to certain non-B mtDNA structures (Lyonnais et al 2017). Recently, a study using a combination of high resolution microscopy and cell biology techniques revealed that TFAM coats the mtDNA in a dose-dependent manner, and that TFAM molecules bind the mtDNA approximately every 8 bp (Kukat et al 2015).…”
mentioning
confidence: 99%
“…In addition, the asymmetric mode of mtDNA replication, which remains to some extent controversial, involves intervals of single-stranding of the parental H-strand (38). TFAM, the ubiquitous mtDNA binding protein, has high affinity for GQ DNA (39). The Pif1 helicase, which is resident in the mitochondrial matrix, is stimulated by the presence of GQ and may interact and unwind the structures (40,41).…”
Section: Discussionmentioning
confidence: 99%